ACHIEVEMENT MOTIVATION TRAINING UNTUK MENINGKATKAN MOTIVASI BERPRESTASI PADA GURU SEKOLAH ANAK BERKEBUTUHAN KHUSUS YANG MENGALAMI BURNOUT - Mulya Virgonita; Fitria Linayaningsih (Universitas Semarang, 2017)
T his study aims to determine empirically the influence of Achievement Motivation Training on achievement motivation in elementary school teachers in learning disabilities in Semarang experiencing Burnout. The research subjects were 10 people. The profession as a teacher for children with learning disabilities and special needs is very vulnerable to burnout. High job demands, unrealistic expectations of parents on the work of teachers often lead to stress that affect the performance. It takes a high achievement motivation to overcome this. In this research the method used is the experimental method, with pre-test design of post-test without control group where the subjects of the study were treated in the form of Achievement Motivation Training to see the effect on achievement motivation and measured before treatment and after treatment. The result of the research analyzed by SPSS version 20 shows that there is contribution of Achievement Motivation Training 34,3% to the achievement motivation to teacher, meaning that there are other factors that influence achievement motivation for elementary school teacher for children with special needs.